Perancangan Sistem Informasi Lokasi Klinik Kecantikan Berbasis Web - Kartono; Kristina; Beata Vitri Yanti (LPPM Universitas Widya Dharma Pontianak, 2025)
Beauty clinic is a place that provides various beauty treatment and skin health services for the people around Pontianak City. Some customers have limited access to information and the locations of beauty clinics around them. Therefore, this study aims to design a web-based Location Information System by utilizing the Google Maps API to map beauty clinics in Pontianak City. This research employs a descriptive research design and data collection methods through observation and literature studies. For system requirements analysis and system design, the author uses Unified Modeling Language (UML), while system design applications include Visual Studio Code, XAMPP, MySQL, PHP, HTML, JavaScript, and Google Maps API. This system can help customers find the nearest beauty clinic based on their location and obtain detailed information about the services available at each clinic. Additionally, the system offers a comparison feature between clinics based on distance, type of services, and customer reviews, making it easier for users to make informed decisions. The aim of this study is to develop a Location Information System website that displays the locations of beauty clinics in Pontianak City. This website is expected to be a solution for the people of Pontianak in finding beauty services that match their needs. Moreover, this system is expected to improve time efficiency and customer accessibility in obtaining beauty service information.